Animation in Science Learning with Brain Based Learning Models to Improve Student Learning Outcomes - Wulansari, Ni Kadek Ayu Mita; Suarni, Ni Ketut (Universitas Pendidikan Ganesha, 2020)
The problems of this study are: the lack of maximum mastery of educators on innovative learning models and media, students are burdened with a lot of material without any pause to give the brain time to process the material provided, learning is less effective and well thought out, discussed useful and active students in the learning process, learning that takes place in the class that is less influential on student learning outcomes. The brain-based learning model of animation-assisted learning of science learning outcomes. This research is a quasi-experimental study, with the design of Nonequivalent Control Group Design. The population of this research is all of the fifth-grade elementary school with 129 students. The method of collecting data in this study is a test method in the form of a multiple-choice test that has been validated. Data were analyzed using a t-test. The results of data analysis obtained t-count = 9.66 at a significance level of 5% and db = 68 obtained t-table = 2.00 so t-count = 9.66> t-table = 2.00. Thus, it can be concluded that there is an influence of an animation-based brain-based learning model on science learning outcomes. Animated brain-based learning model can be applied to science lessons in elementary school as an effort to improve student learning outcomes optimally in science learning